(untitled) (The Pakistan Development Review, 1999)
The paper argues against the currently fashionable case for “state minimalism”. It argues for a strong, activist state, though operating on a different basis and in different areas from the many recently failed interventionist states and many developing countries. The paper seeks to rescue alternative perspectives, such as the importance of the “civil society” that cuts across national boundaries. Global participation is examined. “Market-friendly” interventions are welcomed only if they are “people-friendly”. The role of the civil society, the problems of the post-socialist countries and the role of the fashionable slogans privatisation, liberalisation, deregulation and decentralisation are analysed. These are seen to call for many qualifications. The links between democracy, capitalism and development are reviewed. The social capital of trust and reciprocity that is invested in norms and networks of civic life is seen as a vital factor of effective government and economic progress. Should economic reform precede political reform in the countries in transition? Some lessons can be learned for the developing countries from the countries in transition. An analysis of the politics and the political economy of development aid follow. Buffers between donors and recipients are suggested, such as mutual monitoring of each other’s performance by recipients, a council of wise men and women, or a secretariat with genuinely global loyalties. A quiet style in aid-giving is also an option, when potential improvers are rewarded, without the imposition of conditionality. The paper then goes on to a presentation of various theories of the state. A non-maximising theory is recommended. It ends with a set of policy conclusions for governments and for aid agencies.